Pengenalan Wayang Kulit Menggunakan Teknologi Virtual Reality Berbasis Mobile - I Made Rama Pratama; Subari (Ikatan Ahli Informatika Indonesia, 2021)
Wayang kulit is a native Indonesian culture that was recognized by UNESCO in 2003. As the next generation, the Indonesian people should be able to preserve Indonesian culture so that it does not become extinct or be stolen by other countries. This makes researchers get the idea to preserve culture in an easy-to-understand way, by creating an application for introducing wayang kulit on smartphones using virtual reality technology. In this study, the researcher applied the Waterfall Software Development Life Cycle (SDLC) research procedure and collected data by observation and literature study. Researchers use Unity 3D as a game engine and Blender as a 3D object modeling. The basic concept of this application is that the user will be in a virtual room that has several wayang kulit in it so that users can feel the atmosphere in the wayang kulit gallery. This application has 3 main features: viewing; reading the information; and holding wayang kulit. To run this application better, users are advised to use VR glasses and a VR remote. Researchers hope that this application can be used as a medium for introducing wayang kulit for Indonesian people, especially for the younger generation.